A Photowelding Strategy for Conductivity Restoration in Flexible Circuits. (28th November 2019) - Sun, Yunyu; Yang, Mingcheng; Guo, Yutong; Cheng, Mengjiao; Dong, Bin; Shi, Feng
Abstract: Light‐driven micropumps, which are based on electro‐osmosis with the electric field generated by photocatalytic reactions, are among most attractive research topics in chemical micromotors. Until now, research in this field has mainly been focused on the directional motion or collective behavior of microparticles, which lack practical applications. In this study, we have developed a photowelding strategy for repeated photoinduced conductivity recovery of cracked flexible circuits. We immersed the circuit in a suspension of conductive healing particles and applied photoillumination to the crack; photocatalysis of a predeposited pentacene (PEN) layer triggered electro‐osmotic effects to gather conductive particles at the crack, thus leading to conductivity recovery of the circuit. This photowelding strategy is a novel application of light‐driven micropumps and photocatalysis for conductivity restoration. Abstract : Flicken und Biegen : Die pentacenbasierte Photokatalyse wurde zur Wiederherstellung der Leitfähigkeit von flexiblen Schaltungen eingesetzt (geprägtes Photoschweißen). Die photoinduzierte Ladungstrennung und die daraus resultierenden photokatalytischen Produkte, die nahe der bestrahlten organischen Halbleiterschicht erzeugt wurden, ermöglichten die Agglomeration des Heilmittels an der beschädigten Stelle und so deren erfolgreiche Reperatur.